Evolution of mammal epigenetic control systems - Graves, Jenny (Henry Stewart Talks, 2007)
How, when and why did epigenetic silencing evolve in mammals?, examination of two mammal-specific systems, genomic imprinting and X-chromosome inactivation, from an evolutionary standpoint, using comparisons between humans, distantly related mammals (marsupials and monotremes) and other vertebrates, independent evolution of imprinting in different genomic regions and correlation with evolution of viviparity, step-wise evolution of the elements of the complex X-chromosome inactivation mechanism, shared features of imprinting and X-inactivation
Archived at 2017/10/16